2015
DOI: 10.1097/id.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Is It Safe to Reuse Dental Implant Healing Abutments Sterilized and Serviced by Dealers of Dental Implant Manufacturers? An In Vitro Sterility Analysis

Abstract: Reuse of healing abutments can be cost effective in dental practice. However, used abutments sterilized and serviced by dental implant dealers might be a source of cross-infection. They should therefore be cleaned and resterilized before reuse as a precaution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 19 publications
3
33
0
3
Order By: Relevance
“…Some companies also collect these used components, clean sterilize and repackage them for sale. 1 Studies have confirmed that titanium HAs can be adequately sterilized, 2 and in some instances the form of sterilization can produce an increase in soft tissue cell adhesion and spread over a clean titanium surface. 3,4 However, recent studies have indicated that some of these components may not be as clean or sterile as previously thought and questioned the safety of re-use.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some companies also collect these used components, clean sterilize and repackage them for sale. 1 Studies have confirmed that titanium HAs can be adequately sterilized, 2 and in some instances the form of sterilization can produce an increase in soft tissue cell adhesion and spread over a clean titanium surface. 3,4 However, recent studies have indicated that some of these components may not be as clean or sterile as previously thought and questioned the safety of re-use.…”
Section: Introductionmentioning
confidence: 98%
“…HAs are generally designated by the manufacturer for single use, though it is common practice that many clinicians clean and sterilize this component, often re‐using (recycling) it for economic reasons. Some companies also collect these used components, clean sterilize and repackage them for sale . Studies have confirmed that titanium HAs can be adequately sterilized, and in some instances the form of sterilization can produce an increase in soft tissue cell adhesion and spread over a clean titanium surface .…”
Section: Introductionmentioning
confidence: 99%
“…In dentistry, there are several devices that are reused across patients encompassing all dental specialties, such as surgical instruments, burs, bone saws, endodontic files, periodontal instruments, orthodontic devices, x‐ray holders, and several instruments in pediatric dentistry. In implant dentistry, common examples of ad‐hoc reusable devices include surgical instruments, surgical handpieces, surgical drills, bone cutting burs, impression copings, and many more . Examples of in‐situ reusable devices in implant dentistry include healing abutments, cover screws, abutments, abutment screws, and prosthetic screws.…”
mentioning
confidence: 99%
“…By definition, healing abutments and cover screws are “in‐dwelling” or in‐situ interim devices, and healing abutments and cover screws have traditionally been reused by dentists for economic reasons . However, the definitions for healing abutments and cover screws as defined by the Glosssary of Oral and Maxillofacial Implants and the Glossary of Prosthodontic Terms do not specify whether they are reusable.…”
mentioning
confidence: 99%
See 1 more Smart Citation